Analytical Method Validation of Sildenafil Citrate and Caffeine in Herbal Medicine for Increasing Stamina using Thin Layer Chromatography - Densitometry - Diana, Diana; Rena Octaria; Henry Kurnia Setiawan (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Traditional medicine has been believed for generations to be effective in treating various diseases and is recognized for its safety. One reason people opt for herbal medicine is its affordability compared to chemical drugs. Additionally, herbal medicine is required to be free of medicinal chemicals (BKO). However, a public warning issued between 2020 and 2025 indicated that some herbal preparations still contained substances like sildenafil citrate and caffeine. The aim of this research is to establish a validated analytical method to detect the presence of sildenafil citrate and caffeine in stamina-enhancing herbal medicines using Thin Layer Chromatography (TLC) with densitometry. This method was selected due to its cost-effectiveness and its ability to separate two compounds. In this study, category II validation was conducted to identify impurities in the preparations, focusing on test parameters such as selectivity and Limit of Detection (LOD). The selected mobile phase for this study was a mixture of chloroform and ethanol (9.5:0.5 v/v). The TLC plate was analyzed with a densitometer at a wavelength of 254 nm. The Rf value for sildenafil citrate was found to be 0.32, while the Rf value for caffeine was 0.52, resulting in a separation (Rs) value of 2. The LOD for sildenafil citrate was determined to be 8.5418 μl/ml (equivalent to 0.0854 mg in a 600 mg sample), whereas the LOD for caffeine was 4.7987 μl/ml (or 0.0959 mg in a 600 mg sample).